The study of “mei” (美) from the perspective of archaeological evidences / Wong Hoong Cheong, Goh Ying Soon and Yap Soh Leay - Wong, Hoong Cheong; Goh, Ying Soon; Yap, Soh Leay (UiTM Cawangan Johor Kampus Pasir Gudang, 2020)
The Chinese character "mei"(美) carries out the meaning of beauty in Chinese, but “mei” in Chinese oracle bone inscriptions (甲骨文) and Chinese bronze inscriptions (金文) do not reflect the meaning of beauty as it basically related to the names of places and the names of people only. The East Han dynasty, Shuowen Jiezi (《说文解字》) had denoted the meaning of “mei” as sweetness (甘), but there are still lots of arguments concerning the meaning of this Chinese character “mei” until now. Besides, the creation of the Chinese character “mei” (美) is a topic that has been explored by many researchers and scholars which resulted in various interpretation of the character by them. The archaeological evidences were presented as focuses of discussion. It is hoped that the discussion of this paper is able to contribute to the teaching and learning of pure Chinese linguistics courses such as semantics, ancient Chinese studies and related courses.